Combination Of Aspergillus Niger Fermentation And Broken Rice As Coagulant For Treatment Of Palm Oil Mill Effluents - Kamaludin, Ramizah (2023)
One of the biggest issues faced by the palm oil industry is the released POME in their daily production. Prior to being released into the environment, palm oil mill effluent (POME) is frequently treated at industrial scale using ponding systems. The primary goal of this study was to treat POME prior discharge into environment at established standard limit. When Aspergillus niger was used to treat the collected POME, its critical parameters, including chemical oxygen demand, total suspended solids, phosphorus content, ammoniacal nitrogen content, and its amylase activity, were monitored throughout the fermentation. Before starting the fermentation of the POME in the 2.5 L stirred-tank bioreactor, the POME was pretreated with various sonification frequencies. The POME fermentation in the shake flask was initially carried out by varying the pH value. The pH and the sonification frequency were used as a pretreatment before starting the biological treatment. The best pH value and sonification frequency with the highest chemical oxygen demand (COD) removal percentage was then selected. The secondary treatment, which involves the coagulation treatment utilizing broken rice as the natural coagulant, was also continued on the treated POME. The influence of temperature, pH, curing time, and broken rice dose was assessed for this treatment's coagulation via optimization using one-factor-at-a-time (OFAT).